The Assistancing of The Covid-19 Alert Village Antasan Kecil Timur - Akhmad Syakir (Borneo Community Development, 2021)
The low level of public awareness in the village of Antasan Kecil Timur regarding the dangers of spreading the covid-19 virus is of particular concern in community service by Field Supervisory Lecturers (DPL) and the KKN 7 team at the Muhammadiyah University of Banjarmasin. From the survey results in the field, the focus of the community service is assistance in the village of Antasan Kecil Timur as follows: 1) Socialization and Education on How to Wash Hands, 2) Distribution of Masks and Handbags, 3) Distribution of Vitamin C, and 4) Making Herbal Gardens, 5) Making Posters and Short Videos of Covid-19 Prevention. There are two methods used in this implementation, namely, the method of socialization and education. The results of this Community Service show that, to increase public awareness of the dangers of covid-19 transmission, it is necessary to have real assistance from either the government or local village officials. During the mentoring, it shows the awareness of the community to always use masks when going out of the house, and the importance of maintaining cleanliness, washing hands, in managing herbal plants.